Digital Literacy and The Changing Landscape of The Accounting Profession: The Role of Technology Adoption Model - Luluk Muhimatul Ifada; Acep Komara (Jurnal Kajian Akuntansi, 2023)
AbstractThe aim of this research is to find out the current changes in the accounting professional landscape,that is the digitization of the accounting profession and the importance of digital literacy to deal with it, and how the technology adoption model mediates this relationship. Auditors at the Public Accounting Firm (KAP) Central Java Indonesia became the object of this study, a total of 21 Public Accounting Firms. This study uses purposive sampling method with sampling criteria respondents having work experience as an auditor for more than 3 years. Data collection uses a questionnaire distributed via Google from and paper. Multiple regression analysis is used in hypothesis testing, by testing the validity, reliability and classical assumption tests. The results of the study show digital literacy has a beneficial and significant impact on digitization in the accounting profession. Digital literacy, on the other hand, has no effect on technology adoption models. In addition, the Technology adoption model has a beneficial and significant impact on digitization in the accounting profession. Accountants should improve their digital literacy using thetechnology adoption model to make effective, accurate and relevant accounting judgments. This research has a novelty in the concept of mediating the technology adoption model in increasing the effect of digital literacy on the accounting profession in the context of Public Accountant auditors.Keywords: Accounting profession; Digitalization; Digital literacy; Technology adoption models.AbstrakTujuan dari penelitian ini adalah untuk mengetahui perubahan lanskap profesional akuntansi saat ini yaitu digitalisasi profesi akuntansi dan pentingnya literasi digital untuk menghadapinya, serta bagaimana model adopsi teknologi memediasi hubungan tersebut. Auditor di Kantor Akuntan Publik (KAP) Jawa Tengah Indonesia menjadi objek pada penelitian ini, sejumlah 21 Kantor Akuntan Publik. Penelitian ini menggunakan metode purposive sampling dengan kriteria pengambilan sampel responden memiliki pengalaman kerja sebagai auditor lebih dari 3 tahun.  Pengumpulan data menggunakan kuesioner yang di sebarkan melalui google from maupun hardcopy. Analisis regresi berganda digunakan dalam uji hipotesis, dengan melakukan pengujian validitas, reliabilitas dan uji asumsi klasik. Hasil penelitian menunjukkan literasi digital memiliki pengaruh yang positif dan signifikan terhadap digitalisasi dalam profesi akuntansi. Literasi digital, di sisi lain, tidak berpengaruh pada model adopsi teknologi. Selain itu, model adopsi Teknologi memiliki pengaruh yang positif dan signifikan terhadap digitalisasi dalam profesi akuntansi. Akuntan harus meningkatkan literasi digital mereka menggunakan teknologi dalam pemeriksaan akuntansi yang efektif, akurat, dan relevan. Penelitian ini memiliki kebaruan dalam konsep mediasi Model Adopsi Teknologi dalam meningkatkan pengaruh literasi digital terhadap profesi akuntansi dalam konteks auditor Akuntan Publik.Kata Kunci: Digitalisasi Profesi Akuntansi; Literasi Digital; Model Adopsi Teknologi.